2018
DOI: 10.1155/2018/9790303
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Dantrolene and Nimodipine on the Phenylephrine-Induced Contraction and ACh-Induced Relaxation in Aortic Rings from Diabetic Rats

Abstract: Diabetics have a higher risk of developing cerebral vasospasms (CVSP) than nondiabetics. The addition of the ryanodine receptor (RyR) blocker dantrolene to standard therapies reduces vasospasms in nondiabetics. Whether diabetics with CVSP also benefit from this drug, however, is unknown. We evaluated the effects of a 30 min incubation with dantrolene (50 μM), nimodipine (50 nM), and both drugs in combination, on phenylephrine- (PHE-) induced contraction and on acetylcholine- (ACh-) induced relaxation in aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 30 publications
(20 reference statements)
0
14
2
Order By: Relevance
“…The reduction of contractility is dose-dependent. Previously, we reported that these two drugs, when combined, improve endothelial-dependent relaxation and reduce PHE-induced contraction in diabetic rats 16 , 17 . The findings of the current study are relevant to SAH patients because bleeding is associated with higher release of 5-HT, which is an important contributor to the etiology of CVSP 26 .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The reduction of contractility is dose-dependent. Previously, we reported that these two drugs, when combined, improve endothelial-dependent relaxation and reduce PHE-induced contraction in diabetic rats 16 , 17 . The findings of the current study are relevant to SAH patients because bleeding is associated with higher release of 5-HT, which is an important contributor to the etiology of CVSP 26 .…”
Section: Discussionmentioning
confidence: 93%
“…These treatments, however, do not effectively block the neurological deterioration observed after CVSPs 26 . The addition of dantrolene to standard therapies may improve neurological outcomes in diabetic patients because of their dual effect in reducing vascular contractility and improving endothelial- dependent relaxation throughout reduction of the lipid peroxidation markers MDA and 4-HAE in diabetic rats 16 . Thus, by acting additionally as an antioxidant agent, dantrolene may contribute to reduced neuroinflammation, which plays an important role in the pathogenesis of SAH, and improve stroke manifestations in diabetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three subtypes of the RyR family (RyR1, RyR2, and RyR3) are present in the VSM of the thoracic aorta [16], the mesenteric arteries [14], the large cerebral arteries [17], and the cerebral microcirculation [4]. Dantrolene effectively blocks all the RyR subtypes [18,19], reduces malondialdehyde (MDA) levels [20,21], and provides neuroprotection by increasing the antioxidant defenses in spinal cord-injured rats [22]. Moreover, concomitant administration of dantrolene and nimodipine significantly decreases serotonin-induced contraction in isolated basilar and femoral arteries of rats [23], which suggests that the combined use of these drugs reduces the incidence and severity of CVSPs by simultaneously blocking Ca +2 entry through the L-type VDCC and Ca +2 release by RyR from the SR.…”
Section: Introductionmentioning
confidence: 99%